MORPHOMETRIC FEATURES OF THE THYMUS STRUCTURE DUE TO THE INFLUENCE OF XENOBIOTICS - Shyian, Denis; Avilova, Olga (The Ukrainian Scientific Medical Youth Journal, 2017)
Nowadays scientific achievements in various areas of lives have caused the creation of more and more «foreign body substances» known as xenobiotics. Different chemicals have the detrimental effect on the body systems and, thus, all humanity. The purpose of this work is to determine the alterations of the white rats’ organometric indexes of the thymus after xenobiotic induction in 1/10 and 1/100 LD50doses with the average lethal dose in 5,75 g/kg of the body. For the study was chosen commonly used polyether that belongs to a group of «Laproxides» - tryglycidyl ether of polyoxypropylene triol. The research presents a theoretical generalization of the experiment results and establishes the mechanism of action of this xenobiotic. Were used morphometric, mathematical and statistical methods. The morphometric investigation revealed the size reduction of the thymus after chemical induction on 7th, 15h, 3Cfh day with the high degree of authenticity that was proved by the changed morphometric parameters of the organ - weight, length, breadth, thickness. The analysis of the obtained results allows to state that this substance, in conditions of the oral administration to the body in the above mentioned doses, can lead to atrophy and thymus dysfunction